Carbon density and sequestration in the temperate forests of northern Patagonia, Argentina - Loguercio, Gabriel A.; Simon, Alois; Winter, Ariel Neri; Ivancich, Horacio; Reiter, Ernesto J.; Caselli, Marina; Heinzle, Facundo G.; Leuschner, Christoph; Walentowski, Helge (Frontiers in Forests and Global Change, 2024)
Introduction Forests are a crucial part of the global carbon cycle and their proper management is of high relevance for mitigating climate change. There is an urgent need to compile for each region reference data on the carbon (C) stock density and C sequestration rate of its principal forest types to support evidence-based conservation and management decisions in terms of climate change mitigation and adaptation. In the Andean Mountains of northern Patagonia, extensive areas of temperate forest have developed after massive anthropogenic fires since the beginning of the last century. Methods We used a plot design along belt transects to determine reference values of carbon storage and annual C sequestration in total live (above- and belowground biomass) and deadwood mass, as well as in the soil organic layer and mineral soil (to 20 cm depth) in different forest types dominated by Nothofagus spp. and Austrocedrus chilensis. Results Average total carbon stock densities and C sequestration rates range from a minimum of 187 Mg.ha−1 and 0.7 Mg.ha−1.year−1 in pure and mixed N. antarctica shrublands through pure and mixed A. chilensis forests taller than 7 m and pure N. pumilio forests to a maximum in pure N. dombeyi forests with 339 Mg.ha−1 and 2.2 Mg.ha−1.year−1, respectively. Deadwood C represents between 20 and 33% of total wood mass C and is related to the amount of live biomass, especially for the coarse woody debris component. The topsoil contains between 33 and 57% of the total estimated ecosystem carbon in the tall forests and more than 65% in the shrublands, equaling C stocks of around 100–130 Mg.ha−1 in the different forest types. Conclusion We conclude that the northern Patagonian temperate forests actually store fairly high carbon stocks, which must be interpreted in relation to their natural post-fire development and relatively low management intensity. However, the current high stand densities of these forests may well affect their future carbon storage capacity in a warming climate, and they represent a growing threat of high-intensity fires with the risk of a further extension of burned areas in the future.